FROST INVESTIGATION 1944-1945. APPENDIX 14. REPORT ON LABORATORY AND FIELD TEST PROCEDURES. PART 1. MISSOURI RIVER DIVISION. PART 2. GREAT LAKES DIVISION. PART 3. BOSTON DISTRICT. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1945)
The report describes test methods and procedures used for investigation of frost action beneath airfield pavements in selected areas of the United States. See also Appendix 13, AD-712 471, and Appendix 15, AD-712 470.